(untitled) (Journal of Hama University, 2021)
This study aimed to isolate and purify Clostridium perfringens from chicken flocks in order to detect the existence of Alpha and Net B toxin gens by PCR. These toxins are considered as the most important virulent factors of Clostridium perfringens in chickens. The results of the isolation of Clostridium perfringens in necrotic enteritis infected flocks showed that the isolation percentage was % 24.47 in broiler flocks and it was % 17.41 in breeder flocks. While it also showed that the isolation percentage in healthy flocks was % 5. The result of the PCR test showed the existence of Alpha toxin gens in all the isolates that were received from infected and healthy birds. Whereas, Net B toxin gene was existed only in the isolates that were received from infected birds with the percentage of %11.62. On other hand, the netB gen was never existed in the isolates that were received from healthy birds. This study has proved that the NetB toxin gene exists in the isolates that were received from infected flocks by necrotic enteritis in Syria. The NetB toxin is considered as the most important violent factors of Clostridium perfringens.